RETRACTED: MODELS OF DEVELOPMENT OF THE ENTERPRISES IN THE CONDITIONS OF INTERFIRM COOPERATION - K. D. Busygin (Модернизация, инновация, развитие, 2015)
Retracted articleThe relevance of this study is due to the fact that the current situation inRussiais complemented by the negative effects of market reforms in the economy and economic sanctions taken against our country and in particular companies at various levels. In view of this, for the effective management and development activities of companies and enterprises of various forms of ownership in terms of inter-firm cooperation are highly relevant issues related to economic and mathematical modeling of the development and management decisions. Simulation allows you to not only qualitative and quantitative evaluation of the effectiveness of financial and economic activity of the organizations, but also to evaluate the effectiveness of decisions aimed at ensuring the orderly functioning and development of these organizations.